KETENTUAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM PASAL 74 UU NO. 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS (P.T) SEBAGAI ZAKAT TIJARAH PERSPEKTIF AL-MASLAHAH AL-MURSALAH - Nurul Akbar (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2014)
In this study concluded that the provisions of the Corporate Social Responsibility (CSR) in Article 74 of the Law. No. 40 of 2007 on Limited Liability Company (PT), any item that is traded by humans such as silver, livestock, industry, and the stock compulsory Zakat, it is consistent with the results of the First International conference in Kuwait (29 Rajab 1424 AH), because the company belong Syakhsan I’tiba>ran or Syakhsan Huku>miyah, and was reinforced in Law No. 23/2011 on the management of zakat, Chapter I, article 04 stated that among the objects that must be issued zakat zakat is trade and enterprise. Meanwhile, if viewed in the perspective of maslahah al-mursalah, in the context of maslahah al-mursalah, Company which carries on business in the field of natural resources, or which carries on business related to natural resources. Duty to be responsible for the social problems faced by the local community and shall carry out its social and environmental responsibility. This is in accordance with the Company Law No. 40 of 2007 Article 74 paragraph (4) and in government regulation (PP) No. 47 in 2012. That's all for the benefit of the local community and avoid kemudharatan limited liability company whose environment is used for events and activities of the limited liability company.